2014
DOI: 10.1002/anie.201402986
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics versus Kinetics in Nanosynthesis

Abstract: One may discover a stone tool by chance but it takes more than luck to make a car or cell phone. With the advance of nanoscience, the synthesis of increasingly sophisticated nanostructures demands a rational design and a systems approach. In this Review, we advocate the distinction between thermodynamically and kinetically controlled scenarios, that is, whether a product forms because it is the most stable state or because the pathway leading to it has the lowest energy barrier. Great endeavours have been made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
455
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 436 publications
(463 citation statements)
references
References 302 publications
(260 reference statements)
2
455
0
6
Order By: Relevance
“…According to the previous studies, the average surface energies of different facets of perovskite crystals follow the order of {111} > {110} > {100} [23−27]. Thus, NaTaO 3 cubes with low-energy {100} facets prefer to form at low ratio of EG to water (i.e., low supersaturation), which is likely to be a thermodynamic controlled scenario [7]. While, CTC with high-energy {111} facets can be obtained at relatively high ratio of EG to water (i.e., high supersaturation).…”
Section: Science China Materialsmentioning
confidence: 96%
See 1 more Smart Citation
“…According to the previous studies, the average surface energies of different facets of perovskite crystals follow the order of {111} > {110} > {100} [23−27]. Thus, NaTaO 3 cubes with low-energy {100} facets prefer to form at low ratio of EG to water (i.e., low supersaturation), which is likely to be a thermodynamic controlled scenario [7]. While, CTC with high-energy {111} facets can be obtained at relatively high ratio of EG to water (i.e., high supersaturation).…”
Section: Science China Materialsmentioning
confidence: 96%
“…Especially, it is still a great challenge to explore some universal, precise surface-controlling strategies that apply to most crystalline materials from metallic to ionic and even molecular crystals. Establishing the mechanistic proposals on the basis of thermodynamics and kinetics principles and concepts, which are universal for the growth of macroscopic and microscopic crystals, is the first step towards a rational design and systematic approach [6,7]. Recently, based on thermodynamics and the Thomson−Gibbs equation, we concluded that the surface energy of crystal face is in proportion to the supersaturation of crystal growth units during the crystal growth, which can effectively guide the State Key Laboratory of Physical Chemistry of Solid Surfaces, Collaborative Innovation Center of Chemistry for Energy Materials, and College of Chemistry and Chemical Engineering, Xiamen University, Xiamen 361005, China * Corresponding authors (emails: zxxie@xmu.edu.cn (Xie Z); qkuang@xmu.edu.cn (Kuang Q)) control of the surface structure of some crystals [8].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental and theoretical insights have indicated that, in order to produce monodisperse NCs, a discrete, burst-like nucleation event must ideally be combined with a diffusion-controlled growth, and these two reaction stages should be temporally separated (Park et al, 2007;Kwon and Hyeon, 2008;Wang et al, 2015). Within this framework, systematically tuned sizes and narrow size variances can be achieved by balancing the relative consumption of monomers between the nucleation and the growth stages across an appropriately programed time evolution of the monomer concentration.…”
Section: Synthesis Of Single-materials Ncsmentioning
confidence: 99%
“…Within this framework, systematically tuned sizes and narrow size variances can be achieved by balancing the relative consumption of monomers between the nucleation and the growth stages across an appropriately programed time evolution of the monomer concentration. Depending on the particular material target, this dynamics may be realized by applying ad hoc reactant delivery techniques (e.g., a primary swift "hot-injection, " combined with secondary slow additions of extra reactants), by manipulating the unique reactivity of the system (e.g., a "delayed" nucleation event followed by rapid autocatalytic growth), or deliberate promotion of digestive ripening (to promote growth of the larger, more stable nanoparticles at the cost of the spontaneous dissolution of the smallest, unstable ones) (de Mello Donegà et al, 2005;Park et al, 2007;Kwon and Hyeon, 2008;Wang et al, 2015). Importantly, the dynamic binding of organic stabilizers can significantly affect the relative stability of the surface facets enclosing the growing NCs, thereby driving their shaping into non-spherical habits (e.g., cubes, polyhedrons, rods, wires, and polypods).…”
Section: Synthesis Of Single-materials Ncsmentioning
confidence: 99%
See 1 more Smart Citation